THE EFFECT OF INDUSTRIAL AND WASTE FIBERS ON CONCRETE STRENGTH AND STRUCTURAL BEHAVIOR OF RC SHORT COLUMNS - Naser , Maryam; Falah, Mayadah; Naser, Fatimah; Nasr, Mohammed; Hashim, Tameem; Shubbar, Ali (IIUM Engineering Journal, 2024)
Concrete is a brittle substance; thus, it is reinforced with rebars and fibers to enhance its ductility. On the other hand, the presence of waste from various industries negatively impacts the environment. The ongoing reconstruction in Iraq has resulted in an abundance of locally produced rebar-connecting wire (RCW) and copper electric wire (CEW) waste. To minimize the environmental impact of these wastes, they can be reused in other industries, such as the concrete industry. Few studies have dealt with concrete's structural and mechanical properties containing these local residues. Therefore, this study included an experimental investigation of concrete columns with and without various types of industrial and waste fibers. Two types of industrial fibers (macro hooked-end; CH, and micro straight; CS) steel fibers and two types of waste fibers (RCW and CEW) were utilized. Six reinforced concrete (RC) columns (150 × 150 × 450 mm3) were cast: one control column without fibers and five columns with fibers. The fiber content within the columns was fixed at 0.75% of the concrete volume. The cracks pattern, load-deflection behavior and concrete strain for RC columns were investigated. Moreover, the mechanical properties in terms of compressive, splitting tensile, and flexural strengths tests were also conducted. The results revealed that all types of fibers used improved the mechanical and structural properties of the concrete. Moreover, although the hybrid synthetic fibers gave the best improvement compared to the reference sample, the waste fibers (especially RCW) showed a significant improvement that reached 30.91% in relation to the ultimate load and (10.1, 10.8 and 14.4%) in relation to the compressive, tensile, and flexural strengths respectively. ABSTRAK: Konkrit adalah material rapuh; oleh itu ianya dikuatkan dengan besi dan fiber bagi menguatkan kekuatannya. Dalam masa sama, kehadiran bahan buangan dalam pelbagai industri memberi kesan negatif kepada persekitaran. Penstrukturan semula Iraq yang sedang berlangsung memberi kesan kepada kebanjiran bahan buangan seperti besi penghubung litar (RCW) dan litar elektrik tembaga (CEW) buatan tempatan. Bagi mengurangkan kesan pencemaran terhadap alam sekitar, bahan-bahan ini boleh diguna balik dalam industri berbeza, seperti industri konkrit. Terdapat banyak kajian terhadap buangan tempatan yang melibatkan struktur bahan konkrit dan sifat mekanikal. Oleh itu, kajian ini merupakan kajian eksperimen pasak konkrit dengan atau tanpa pelbagai jenis industri dan fiber buangan. Dua jenis fiber industri iaitu fiber besi (mikro hujung-penyangkut; CH dan mikro lurus; CS) dan dua jenis fiber buangan (RCW dan CEW) dipakai. Enam RC pasak konkrit (150 × 150 × 450 mm3) dihasilkan: satu pasak kawalan tanpa fiber dan lima pasak dengan fiber. Kandungan fiber dalam pasak di tetapkan pada 0.75% isipadu konkrit. Corak rekahan, ciri-ciri kesan beban dan tekanan konkrit pada pasak RC dikaji. Tambahan, kajian terhadap ciri-ciri mekanikal berdasarkan tekanan, rekahan tensil dan kekuatan anjalan telah dijalankan. Dapatan kajian menunjukkan kesemua fiber yang digunakan menambah baik ciri-ciri mekanikal dan struktur konkrit. Tambahan lagi, walaupun fiber sintetik hibrid menunjukkan paling baik berbanding sampel contoh, fiber buangan (terutama RCW) menunjukkan pembaharuan ketara mencapai 30.91% berbanding beban maksimum dan masing-masing menunjukkan 10.1, 10.8 dan 14.4% pada tekanan, rekahan tensil dan kekuatan anjalan.